A new species of Dolomedes Latreille, 1804 (Araneae: Lycosoidea: Pisauridae) from Madagascar - Da Silva, Estevam L. Cruz; Griswold, Charles E. (Zootaxa, 2013)
The genus Dolomedes Latreille, 1804 present a very wide range of distribution on every continent except Antarctica (Platnick 2013) However, only one species has been reported from Madagascar, Dolomedes saccalavus Strand, 1907, which is unfortunately based on a juvenile specimen and was destroyed in wartime. We consider this a nomen dubium.